A Noble-Metal-Free Heterogeneous Photosensitizer-Relay Catalyst Triad That Catalyzes Water Oxidation under Visible Light - Ghobadi, T. Gamze Ulusoy; Yildiz, Elif Akhuseyin; Buyuktemiz, Muhammed; Akbari, Sina Sadigh; Topkaya, Derya; Isci, Umit; Dede, Yavuz (Wiley-V C H Verlag Gmbh, 2018)
An entirely earth-abundant chromophore-relay water oxidation catalyst triad system, which is robust and efficient at neutral pH, is presented. The synthesis involves the coordination of a porphyrin derivative to a bridging Fe(CN)(5) group, which is then reacted with Co ions to prepare a covalently linked chromophore-Prussian blue analogue assembly. Light-driven water oxidation studies in the presence of an electron scavenger indicate that the triad is active and it maintains a steady activity for at least three hours. Transient absorption experiments and computational studies reveal that the Fe(CN)(5) group is more than a linker as it takes part in electron-transfer and co-operates with porphyrin in the charge separation process.
Keywords: dye-sensitization; porphyrins; Prussian blue; water oxidation; water splitting